Parceria Público Privada e o Programa de Aceleração do Crescimento: geração de emprego no município de Araraquara - Porcionato, Gabriela Lanza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this study, the main objective was to take stock of the Law of ParceriaPúblico-Private in Brazil, 11.079, as well as understand the discussions that culminated in this 2004 and the 2010 Law Law No. 12,349 that caused legal changes in this legal framework . Was also carried out a mapping in the city of Araraquara federal program implemented by the government in 2007, the PAC - Growth Acceleration Program, in which the city receives investment from first year.The CAP is legal support in the PPP law to contract for implementation of national infrastructure works, with this, the research behind a discussion about the state's role remodeling in the previous decade and after the program and to the law, as well as discuss the impact of public policy in the city as the generation of employment and income and also the interactions and tensions around the main agents responsible for implementation, financing and execution of the works, namely, government officials, representatives of private sectors and workers. The research was a survey of the services sector in the city, collecting data on the labor ministry site, the session city profile which contains information about the absolute change in employment in the city. The research, which was inspired by the book Between Solidarity and Risk: unions and pension funds in Lula Government of times, written by Prof. Dr. Mary A. Chaves Garden considered the PPP Act and the CAP as tools, like pension funds, social inclusion through the market in order to generate employment and income .. the conclusions seek to reflect on the amendment of the 2002 post election government's role, the generation of employment and income at the micro level: city of Araraquara and about ambiguities, limits, tensions and contributions of this relationship between the public and the private

No presente trabalho, o objetivo principal consistiu em fazer o levantamento da Lei de Parceria Público-Privada no Brasil, nº 11.079, assim como compreender as discussões que culminaram nesta Lei de 2004 e na Lei de 2010, nº 12.349 que causou alterações legais neste arcabouço jurídico. Também foi realizado um mapeamento na cidade de Araraquara do programa federal implantado pelo governo em 2007, o PAC - Programa de Aceleração do Crescimento, no qual a cidade recebe investimentos desde primeiro ano. O PAC encontra respaldo legal na lei de PPP para celebrar contratos de execução de obras de infraestrutura nacional, com isso, a pesquisa trás uma discussão acerca da remodelação do papel do Estado na década anterior e posterior ao programa e á lei, assim como, discutir o impacto desta política pública no município quanto a geração de emprego e renda e também as interações e tensões em torno dos principais agentes responsáveis pela implementação, financiamento e execução das obras, sendo eles, representantes do poder público, representantes dos setores privados e trabalhadores. A pesquisa fez o levantamento do setor de serviços no município, coletando dados no site do ministério do trabalho, na sessão Perfil do município onde contém informações sobre a variação absoluta de emprego na cidade. A pesquisa, que teve como inspiração o livro Entre a Solidariedade e o Risco: sindicatos e fundos de pensão em tempos de Governo Lula, escrito pela Prof.ª Drª Maria A. Chaves Jardim considerou a Lei de PPP e o PAC como ferramentas, tal qual os fundos de pensão, de inclusão social via mercado com o objetivo de gerar emprego e renda.. As conclusões buscam refletir sobre a alteração do papel do Estado pós as eleições de 2002, a geração de emprego e renda no nível micro: cidade de Araraquara e acerca das ambiguidades, limites, tensões e contribuições desta relação entre o setor público e o...
Keywords: Parceria público-privada - Brasil; Desenvolvimento econômico; Trabalho - Araraquara (SP); Public-private sector cooperation Brazil